PLANT GROWTH OF EGGPLANT (Solanum melongena L.) IN VITRO IN DROUGHT STRESS POLYETHYLENE GLYCOL (PEG) - Siaga, Erna; Maharijaya, Awang; Rahayu, Megayani Sri (BIOVALENTIA: Biological Research Journal, 2016)
Drought stress is one of the important issues related to the global warming that demand for the development of drought tolerant crops. Eggplant is one of the agricultural commodities which can be developed in dry land so plant growth of eggplant need to be learned. The objectives of this study were to study the effect of several concentrations of polyethylene glycol (PEG) on the in vitro growth of eggplant, and to find the drought tolerant eggplant accessions in dry land. The experimentÂ  was conducted at the Laboratory of Tissue Culture, Department of Agronomy and Horticulture, Bogor Agricultural University. The experiment was laid on a completely randomized design with one factor. The factor was eggplant accessions. The results showed that PEG in vitro media significantly affected the survival percentage, the percentage of callus, developed the bud and the number of leaves of eggplant. Callus in eggplant explants as a way of avoiding drought stress.